2020
DOI: 10.1292/jvms.19-0646
|View full text |Cite
|
Sign up to set email alerts
|

The neuroprotective effect of submicron and blended <i>Lycium barbarum</i> for experiment retinal ischemia and reperfusion injury in rats

Abstract: The purpose of this study was to investigate the neuroprotective potential of submicron (milled) and blended Lycium barbarum (LB) in glaucomatous retinal neuropathy using a rat model of high intraocular pressure (HIOP) induced retinal ischemia. The rats were treated with 500, 250, 100 mg/kg LB (submicron or blended form) orally once daily for 56 days respectively after 1 week of retinal ischemia induction. We conducted electroretinography (ERG), histopathological analysis in retina and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…LBP treatment significantly reduced neuronal death and glial activation in the retina following I/R injury [144,145]. Furthermore, LBP treatment was able to alleviate ischemiainduced retinal dysfunction (exhibiting greater b-wave and oscillatory potential responses) [144,146]. The antioxidant levels (glutathione, SOD and CAT) in the retina were significantly higher, while the MDA level was lower, in the submicron and blended L. barbarum extract-treated groups, compared to the control [146].…”
Section: Lycium Barbarum Lmentioning
confidence: 96%
See 1 more Smart Citation
“…LBP treatment significantly reduced neuronal death and glial activation in the retina following I/R injury [144,145]. Furthermore, LBP treatment was able to alleviate ischemiainduced retinal dysfunction (exhibiting greater b-wave and oscillatory potential responses) [144,146]. The antioxidant levels (glutathione, SOD and CAT) in the retina were significantly higher, while the MDA level was lower, in the submicron and blended L. barbarum extract-treated groups, compared to the control [146].…”
Section: Lycium Barbarum Lmentioning
confidence: 96%
“…Furthermore, LBP treatment was able to alleviate ischemiainduced retinal dysfunction (exhibiting greater b-wave and oscillatory potential responses) [144,146]. The antioxidant levels (glutathione, SOD and CAT) in the retina were significantly higher, while the MDA level was lower, in the submicron and blended L. barbarum extract-treated groups, compared to the control [146]. Further studies demonstrated that LBP exerted its neuroprotective effects via the activation of Nrf2 and an increase in HO-1 protein expression in the retina after I/R injury [145].…”
Section: Lycium Barbarum Lmentioning
confidence: 99%
“…A decrease in GSH levels as a result of I/R was reported to be associated with an increase in LPO in the literature [17] . Wu et al [25] showed that there was a significant decrease in GSH levels in the retinal tissue of rats subjected to I/R, in parallel with the increase in oxidants, compared to the control group. In this study, tGSH levels were significantly decreased in the eye tissue of rats as a result of I/R injury, as has been reported in the literature.…”
Section: Ltc In Ocular Ischemic Syndromementioning
confidence: 99%